218k views
4 votes
Using f(x) =x^2/3-2, determine if each statement below is true or false. Show the work that justifies your answer. The statements are A. F(6)=f(-6) B. F(6)=2 • f(3)

1 Answer

2 votes

Answer:


f(6) = f(-6) --- True


f(6)=2 * f(3) --- False

Explanation:

Given


f(x) = (x^2)/(3) - 2

Solving (a): f(6) = f(-6)

First, we solve for f(6) by substituting 6 for x in
f(x) = (x^2)/(3) - 2


f(6) = (6^2)/(3) - 2


f(6) = (36)/(3) - 2


f(6) = 12 - 2


f(6) = 10

Next, we solve for f(-6) by substituting -6 for x in
f(x) = (x^2)/(3) - 2


f(-6) = (-6^2)/(3) - 2


f(-6) = (36)/(3) - 2


f(-6) = 12 - 2


f(-6) = 10

We have that:


f(6) = f(-6) = 10

Hence, the statement is true

Solving (b):
f(6)=2 * f(3)

We have that:


f(6) = 10

Next, we solve for f(3) by substituting 3 for x in
f(x) = (x^2)/(3) - 2


f(3) = (3^2)/(3) - 2


f(3) = (9)/(3) - 2


f(3) = 3 - 2


f(3) = 1


2 * f(3) = 2 * 1


2 * f(3) = 2

So:


f(6)=2 * f(3)


10 \\eq 2

Hence, the statement is false

User Salal Aslam
by
4.9k points